Unprecedented Rearrangement of β-Difluoroboryloxy Ethers: A Route to C-2 Alkyl-chromenones - Sahoo, Sushree Ranjan; Sarkar, Debayan; Somu, Prathap; Paul, Subhankar; Lönnecke, Peter (Synlett, 2022)
The addition of boron trifluoride etherate (BF3·OEt2) to allenic ketones has led to the isolation of the isolated boron difluoride enolates. The single-crystal structure of boron enolate has been solved. The unprecedented C1–C10 migration of (Z)-β-difluoroboryloxy ether derivatives is observed to deliver rearranged phenol derivatives which are functionalized to C-2 alkyl-chromenones. Interestingly the isolated boron enolates have exhibited significant anticancer properties.
Keywords: enolate; lewis acid; migration; chromenone